Identification and characterization of IgNAR and VNAR repertoire from the ocellate spot skate (Okamejei kenojei) - Wen, Jianqing; Gong, Jinyu; Li, Pengwei; Deng, Penghui; Sun, Mengsi; Wu, Yujie; Tian, Chenxi; Wang, Hao; Bi, Yunchen (Frontiers in Marine Science, 2023)
Elasmobranchs are crucial for comparative studies of evolution, as they belong to the most ancient vertebrate lineages that survived numerous extinction events and persist until today. The immunoglobulin new antigen receptor (IgNAR) found in sharks and heavy-chain-only antibody (HCAb) found in camelidae are products of convergent evolution. Although it was previously believed that IgNAR emerged 220 million years ago, before the divergence of sharks and skates, there is limited evidence to support this. In this study, we provide data supporting the existence of IgNAR in the ocellate spot skate (Okamejei kenojei) mononuclear cell transcriptome and peripheral blood serum. Additionally, we characterize the germline gene configuration of the ocellate spot skate IgNAR V domain. The ocellate spot skate IgNAR structure prediction and VNAR crystal structure exhibit high similarity to their shark counterparts. These data strongly suggest that IgNAR in both sharks and skates share a common ancestor. Sequencing of the ocellate spot skate VNAR repertoire provided crucial data for further understanding of the IgNAR generation. Notably, we discovered that approximately 99% of the ocellate spot skate VNARs belonged to type IV. This represents an exceptionally high proportion of type IV within the VNAR repertoire, which has not been documented in previously studied elasmobranchs. This unique characteristic of the ocellate spot skate VNAR adds essential structural diversity to the naïve VNAR library from elasmobranchs and could potentially benefit the development of pharmaceutical drugs.